The Role of Pesantren Cultural Values in Enhancing Teacher Professional Identity and Commitment - Rasyidin, Rasyidin; Prasetyo, Muhammad Anggung Manumanoso; Naeem, Ayesha Fakhar; Ritonga, Abdullah Sani (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2025)
Purpose -Teacher commitment is a central pillar in improving the quality of education, particularly within the unique ecosystem of Islamic boarding schools (pesantren), where educators play multifaceted roles. this study aims to examine the optimization of permanent instructors' job commitments by focusing on three major aspects: caring, responsibility, and self-discipline. Method -The research method is qualitative, using a phenomenological approach. Data collecting methods include observation, interviews, and documentation studies. The data management process involves data reduction, data display, data analysis, and concluding. The informants included the Pesantren Leader, the Director of Teaching, and two teachers. Findings -The study findings demonstrate that the commitment of pesantren instructors may be established through the hierarchy of strengthening pesantren's cultural values. Pesantren culture is manifested through the five spirits of the pesantren, the most basic of which is the spirit of truthfulness, which forms the pupils' character. Another factor that influences a teacher's dedication is the loyalty that has developed while becoming a student. Pesantren's life cycle involves the regeneration of leadership and instruction. Finally, flexibility in a positive peer environment and a sense of duty for professionalism lead to teacher commitment. Implications - Socially, the findings have consequences for Pesantren's work culture paradigm. The study has societal implications for enhancing the pesantren system through pesantren culture. Originality - this study lies in its cultural perspective on commitment, offering a unique model of educator development based on pesantren values rather than conventional corporate paradigms.